A thermal conductivity model for hybrid heat and mass transfer investigation of single and multi-wall carbon nano-tubes flow induced by a spinning body. (December 2021) - Hussain, Azad; Haider, Qusain; Rehman, Aysha; Ahmad, Hijaz; Baili, Jamel; Aljahdaly, Noufe H.; Hassan, Ali
Abstract: The enhancement of thermal heat transfer utilizing the hybrid nanofluids is explored widely by numerous researchers over the years. Because of these exciting characteristics features of hybrid nanofluids, the prime focus of this article is the investigation of engine oil and mineral oil-based hybrid nanofluids consisting of carbon nanotubes (SWCNT-MWCNT) over a rotating cone present in a convectively heated permeable environment. In the flow supposition, a mathematical model is formulated, Boundary layer approximations are used to minimize the structure of partial differential equations. The dimensionless system of highly non-linear partial differential equations is obtained through boundary layer approximation. The findings obtained showed a rise in temperature for both CNT's, the thickness of the thermal boundary layer has increased under the impact of solid volume fraction of nanotubes. SWCNTs provide a reduction in skin friction and enhancement in Nusselt number. The hybrid nanofluid with EO (engine oil) base has demonstrated a greater heat transfer coefficient and reduced fluid motion's skin friction than MO (mineral oil) based. The model hybrid flow can be used in industries like turbine heat production, wind energy generation, and pharmaceutical processes.